Smith Family Day prize winners on Auditorium steps, Alaska-Yukon-Pacific-Exposition, Seattle, Washington, September 2, 1909 - Nowell, Frank H., 1864-1950 (1909)
Caption on image: The Prize Winners. Smith Family Day. A.Y.P. Exposition. Sept. 2 1909. X3717. Handwritten on verso: From left to right. Oldest pair of twins Smith's: Miss Adna H. and Adeline H. Handsomest Smith man: Mr. E.B. Smith. Handsomest married lady: Mrs. N.H. Smith. Homliest Smith man: Jim P. Smith. Handsomest Miss Smith: Miss. Florence M. Smith. Tallest Smith: Mr. Jack Smith. Shortest Smith: Sidney Smith. Slimest Smith or thinnest: Mrs. Harriet Smith. Fattest Smith: Mrs. W.O. Smith. Youngest Smith twins: Vernon and Vincent Smith. Prettiest Smith baby under one year: William Howard Smith. Prettiest Smith baby over one year: Jeanette Smith. (There is also a poem about the Smith family name proceding the winners names) PH Coll 727.809 To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number